2012
DOI: 10.1111/j.1469-8137.2012.04303.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal methane transport through Juncus effusus: experimental manipulation of morphological barriers to test above‐ and below‐ground diffusion limitation

Abstract: SummaryAerenchymatous plants can transport methane (CH 4 ) from the root zone to the atmosphere, bypassing the surface-oxidizing layers of the soil, yet morphological and anatomical factors that govern the transport of methane have rarely been critically tested in manipulative experiments.Here, we investigated the methane transport capacity of hydroponically grown Juncus effusus, in experiments with roots submerged in nutrient solutions sparged with methane (1.16 mmol CH 4 l À1 ). Through a range of manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 35 publications
(68 reference statements)
0
45
0
Order By: Relevance
“…Kelker and Chanton (1997) suggested it is belowground, at the soil-root or root-shoot boundaries, and that Carex releases CH 4 not through the leaf blades (and stomata) but from the point where the leaves bundle. This would be similar to rice (Oryza sativa), Menyanthes trifoliata, and J. effusus that release CH 4 from the stem or leaf sheath, possibly through micropores, not stomata (Nouchi et al, 1990;Macdonald et al, 1998;Hennenberg et al, 2012). However, in the studies by Schimel (1995) and Morrissey et al (1993), CH 4 seemed to exit the sedges through the leaf blades and stomata, and this would thus form the main resistance for the flux in the plant.…”
Section: Key Factors For Ch 4 Transport and Oxidationmentioning
confidence: 86%
See 1 more Smart Citation
“…Kelker and Chanton (1997) suggested it is belowground, at the soil-root or root-shoot boundaries, and that Carex releases CH 4 not through the leaf blades (and stomata) but from the point where the leaves bundle. This would be similar to rice (Oryza sativa), Menyanthes trifoliata, and J. effusus that release CH 4 from the stem or leaf sheath, possibly through micropores, not stomata (Nouchi et al, 1990;Macdonald et al, 1998;Hennenberg et al, 2012). However, in the studies by Schimel (1995) and Morrissey et al (1993), CH 4 seemed to exit the sedges through the leaf blades and stomata, and this would thus form the main resistance for the flux in the plant.…”
Section: Key Factors For Ch 4 Transport and Oxidationmentioning
confidence: 86%
“…Therefore, they have a large contact surface with the anoxic peat. The area of root surface permeable to gases was the most important factor controlling the CH 4 flux in Juncus effusus, another aerenchymatous species, and this permeable surface is concentrated in fine roots and the tips of coarser roots (Hennenberg et al, 2012). According to Reid et al (2015), the rate for root-mediated gas transport in P. australis and Spartina patens increased during the growing season, indicating increase of permeable root surface area or aerenchyma along the summer.…”
Section: Key Factors For Ch 4 Transport and Oxidationmentioning
confidence: 99%
“…The above-ground biomass per se probably had no effect on the plant-mediated CH 4 emissions, as CH 4 has been shown to be mainly emitted through micropores in the basal parts of rice plants (Nouchi et al, 1990) and through the basal internodes of P. australis (Brix, 1989). Also, Henneberg et al (2012) showed in a manipulation experiment with Juncus effusus that above-ground biomass was unimportant for the CH 4 transport through the plants, whereas the removal of fine roots and root tips of coarse roots led to significant reductions in plant-mediated CH 4 transport. Thus, it is likely that the extensive root system of the reeds at Phrag2 contributed to the high CH 4 emission rates at this site.…”
Section: Ch 4 Emissionsmentioning
confidence: 99%
“…On the other hand, a high primary production also increases the available carbon substrate for methanogens via biomass decomposition and root exudation and can thus lead to higher CH 4 emissions ( Van der Nat and Middelburg, 2000;Whiting and Chanton, 1993). In addition, wetland plants with internal air spaces (aerenchyma) provide an additional gas transport pathway, apart from diffusion and ebullition from the sediment, that can enhance CH 4 emissions (Brix et al, 1996;Henneberg et al, 2012;Sorrell and Boon, 1994). Methane produced in the soil can be transported through the aerenchyma of the plant tissue and bypass the water column, where it otherwise could have been oxidized by methanotrophs before reaching the atmosphere (Whalen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we hypothesized that local hotspots of CH 4 emissions from pastures drained for agriculture could develop in the presence of J. effusus, a wetland plant that can transport gases effectively via its aerenchyma (Henneberg et al, 2012). In wetlands, reports on the importance of aerenchymatous plants for CH 4 emissions differ.…”
Section: Discussionmentioning
confidence: 98%